2017
DOI: 10.1002/adsc.201700928
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diverse Nitrogen Heterocycles via Palladium‐Catalyzed Tandem Azide–Isocyanide Cross‐Coupling/Cyclization: Mechanistic Insight using Experimental and Theoretical Studies

Abstract: A rapid and elegant tandem azide–isocyanide cross‐coupling/cyclization protocol has been developed based on a nitrene transfer reaction. The palladium‐catalyzed ligand‐free methodology led to the synthesis of three different heterocyclic scaffolds with excellent atom/step/redox economy. Studies based on first‐principles‐based quantum calculations and control experiments unraveled a concerted process of nitrene transfer reaction on isocyanides, ruling out the metallaaziridine intermediate reported earlier. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…A domino azide-isocyanide cross-coupling/​cyclization was independently developed by Pardasani’s and Ding’s groups. Their Pd-catalyzed ligand-free methodology allowed the synthesis of three different types of potentially bioactive heterocycles as benzo­oxazinones (with a C–N and a C–O bond formation), quinazolinones (with the generation of two new C–N bonds), and benzazoles (with a C–N and a C–S bond formation).…”
Section: Discussionmentioning
confidence: 99%
“…A domino azide-isocyanide cross-coupling/​cyclization was independently developed by Pardasani’s and Ding’s groups. Their Pd-catalyzed ligand-free methodology allowed the synthesis of three different types of potentially bioactive heterocycles as benzo­oxazinones (with a C–N and a C–O bond formation), quinazolinones (with the generation of two new C–N bonds), and benzazoles (with a C–N and a C–S bond formation).…”
Section: Discussionmentioning
confidence: 99%
“…A Pd(OAc) 2 ‐catalyzed ligand‐free cascade reaction was reported by Sawant and colleagues in 2018 [27] . This methodology was employed to synthesize several types of heterocyclic skeletons by azide−isocyanide cross‐coupling and intramolecular cyclization (Scheme 15).…”
Section: Transition‐metal‐catalyzed Cascade Cyclization Of Azides Iso...mentioning
confidence: 99%
“…A Pd(OAc) 2 -catalyzed ligand-free cascade reaction was reported by Sawant and colleagues in 2018. [27] This methodology was employed to synthesize several types of heterocyclic skeletons by azideÀ isocyanide cross-coupling and intramolecular cyclization (Scheme 15). By detailed experimental and theoretical studies, authors observed that the nitrene transfer to isocyanide was a concerted and turnover-limiting step of the overall route.…”
Section: Pd-catalyzed Cascade Reactionsmentioning
confidence: 99%
“…Analogously, starting from organic azides, the palladium-catalyzed transfers of nitrenes to isocyanide functionalities can be achieved. In a recent example, Sawant et al reported a ligand-free substrate-dependent synthesis of bicyclic systems from bifunctional arylazide substrates [ 89 , 90 ]. Molecular nitrogen is readily extruded from the azide substrates to generate a palladium-bound nitrene intermediate 184 , which is subsequently transferred to the isocyanide to afford the short-lived carbodiimide 185 , which readily undergoes intramolecular addition ( Scheme 49 ).…”
Section: Pd 0 -Catalyzed Isocyanide Insertionsmentioning
confidence: 99%